Control of GaN crystal habit by solution stirring in the Na-flux method. (8th November 2016) - Murakami, Kosuke; Imade, Mamoru; Imanishi, Masayuki; Honjo, Masatomo; Imabayashi, Hiroki; Matsuo, Daisuke; Nakamura, Kosuke; Maruyama, Mihoko; Yoshimura, Masashi; Mori, Yusuke
Abstract: In our previous study, we succeeded in fabricating low-curvature GaN wafers with low dislocation density by the Na-flux coalescence growth technique. However, the crystals consisted of many pyramidal grains with facets, leading to an increase in the oxygen concentration in the crystal, an increase in the lattice constant, and blackening. In this study, we attempted to improve the crystal habit of the GaN crystals by employing a solution-stirring technique in the coalescence growth on multipoint seeds. Scanning electron microscope images indicated that the c -face area became larger by increasing the stirring rate and growth period. We concluded that solution stirring in the Na-flux coalescence growth technique is an effective approach to improve the crystal habit and uniformize the lattice constant of GaN crystals.